Finding Applications for Technologies Beyond the Core Business - Danneels, Erwinn; Frattini, Federico (MIT Sloan Management Review, 2018)
The technologies underlying a company's core businesses can have lucrative applications beyond the ones they provide to current customers. However, many companies don't pursue these opportunities, or do it half-heartedly. Typically, authors Erwin Danneels and Federico Frattini observe, companies are more comfortable developing new products for the customers they already serve than they are with applying their technologies in new markets (a process they call "technology leveraging"). Only a small number of companies make a deliberate effort to tap the potential for business outside their core markets. Using examples from companies the authors have studied or advised, the article describes a four-step process for leveraging technology that involves: (1) characterizing the technology, (2) identifying potential applications, (3) choosing from among the identified applications, and (4) selecting the best entry mode. The first step involves "de-linking" the technology from the specific products in which it is currently used. To do this, the authors explain, companies need to identify the functions the technology can perform. A good characterization can broaden the scope of the potential opportunities and allow people to focus clearly on the technology's abilities and limits. In many settings, this step requires extensive testing and R & D investment. As they explain, "You can't look for new applications until you know what your technology can do vis-à-vis what competing solutions do." Once companies have specified what the technology is, they can begin exploring new settings where it might be applied. Although the authors recommend starting with desk research, the biggest benefits often come from getting out of the office and interacting with people. Trade shows, they say, provide an excellent way to see firsthand where the technology and its alternatives might be applied, and to hear about the pain points of the existing technologies. Another approach is to tap into communities of problem-solvers who might be able to provide suggestions. Although identifying opportunities with the most promise may appear to be straightforward, in practice, the authors note, it can be more involved. Companies often underestimate the challenges of applying the technology, which may be revealed only by building early prototypes. In bringing technology to new markets, the goal should be to find new application areas where your technology performs better on existing pe ...